F-25 алкалоидиНИнг кАЛАМУШ АОРТА ПРЕПАРАТИГА ВАЗОРЕЛАКСАНТ ТАЪСИРИ - Зарипов, А.А.; Усманов, П.Б.; Есимбетов, А.Т.; Абдуллаева, Н.У.; Жўрақулов, Ш.Н. (SCIENCE and SOCIETY, 2023)
In the present work the mechanism of the action of isoquinoline alkaloid F-25 on the Ca2+-transporting system of rat aortic smooth muscle cells has been investigated. Isometric tension forces were recorded using a force transducer FT-03 (Grass Instrument Co., USA). The results of experiments performed under conditions of KCl- and PE-induced contracture indicate that the studied alkaloids have a pronounced relaxant effect, which is based on a decrease in the level of [Сa2+]in in SMC, due to the blockade of the entry of Ca2+ ions through Ca2+L- and Ca2+R-channels.
Keywords: isoquinoline alkaloid; Ca2+-channel; endothelium; vasorelaxant; α-adrenergic receptors